Maintenance of salt barrens inhibited landward invasionofSpartinaspecies in salt marshes - Qi, M. (2020)
Spartinaspp. (cordgrasses) often dominates intertidal mudflats and/or low marshes. The land-ward invasion of these species was typically thought to be restrained by low tidal inundation frequenciesand interspecific competition. We noticed that the reported soil salinity levels in some salt marshes weremuch higher than those at the mean higher high water level, which might inhibit the landward invasion ofcordgrass. To test this possibility, we transplantedSpartina alternifloraacross an elevational gradient in aninvaded salt marsh in the Yellow River Delta National Nature Reserve, where a salt accumulation zone(i.e., salt barren) was previously observed. We found thatS. alterniflorawas significantly inhibited by thesalt barren in high marsh regions, although it performed better at upland and low marsh regions. A com-mon garden experiment further elucidated thatS. alternifloraperformed best at low salinity levels and thatthis species is less sensitive to inundation frequency. Our results indicated that the salt barren inhibited thelandward invasion ofS. alterniflorain salt marshes and provided a natural barrier to protect the uplandfrom invasion. Thoughfield observations suggest thatS. alternifloracould propagate along tidal channels,which provide low-salinity corridors for the dispersal of propagules, natural salt barrens can inhibit thelandward invasion ofSpartinain salt marshes. However, artificial disturbances that break the salt barrenband in salt marshes (e.g., artificial ditches) might accelerate the invasion ofSpartinaspp. This newfindingshould alert salt marsh managers to pay attention to artificial ditches and/or other human activities whenattempting to controlSpartinainvasion.